Fluid biomarkers in familial frontotemporal dementia: progress and prospects - Guo, Mengyao; Qin, Linyuan; Cai, Hanlin; Wang, Ruihan; Luo, Caimei; Yang, Feng; Feng, Shiyu; Gao, Hui; Chen, Qin (Frontiers in Neurology, 2025)
Familial frontotemporal dementia (FTD) is a genetically heterogeneous disease with various clinical manifestations, making it difficult to diagnose. There are three main gene mutations in familial FTD: repeat expansion in chromosome 9 open reading frame 72 (C9orf72), microtubule-associated protein tau (MAPT), and progranulin (GRN). These mutations can produce corresponding changes in fluid biomarkers years before symptoms appear. Therefore, biomarkers play a vital role in the diagnosis and treatment of familial FTD. In this review, we highlight fluid biomarkers in the blood and cerebrospinal fluid (CSF) that contribute to the clinical diagnosis of familial FTD, the study of disease pathophysiological mechanisms, and possibly be used as outcome endpoints in future clinical trials.